Particularism Influence in Theological Search: Implications for Christian-Muslim Dialogue - Opeloye, Muhib O. (2014)
Particularism according to Webster Dictionary' means exclusive or special devotion to a cause. It has political as well as theological significations both of which have similar connotations. .4s a political concept it is a theory or practice advocating a right or freedom for each politically conscious or organised group to promote its own interest without regard for the interest of the target group. In Dopamu's view particularism is the absolute claim of faith; it is an exclusive claim to revelation; it is a weapon used by the exclusivists to see their own faith as the only faith, the one and the only to salvation.